Correction: Cesarean Section and Rate of Subsequent Stillbirth, Miscarriage, and Ectopic Pregnancy: A Danish Register-Based Cohort Study (Public Library of Science, 2014)
Louise Kenny and colleagues conduct a population-based cohort study in Denmark to assess the likelihood of stillbirth, miscarriage, and ectopic pregnancy following cesarean section compared to women who gave birth by vaginal delivery.